Comparative diagnostic accuracy of frozen sections and scrape cytology in ovarian neoplasms - Swati Bhardwaj; Charanjeet Ahluwalia; Amit Kumar Yadav; Sufian Zaheer; Sachin Kolte; Rashmi Arora (Wolters Kluwer Medknow Publications, 2019)
Introduction: Frozen section is a well-established method for providing rapid and accurate intraoperative diagnosis. Cytological techniques such as imprint and scrape cytology and intraoperative fine-needle aspiration cytology are conventionally considered as less accurate alternatives to the frozen section. However, inexperienced hands, scrape cytology has been shown to provide remarkably accurate results comparable to the frozen section. Aims: The aims of this study are as follows: (1) To evaluate the diagnostic utility of scrape cytology in the intraoperative diagnosis of ovarian neoplasms. (2) To compare the accuracy of scrape cytology with frozen section in the intraoperative diagnosis of ovarian neoplasms. Materials and Methods: This study was conducted over a period of 3 years from 2014 to 2017. A total of 60 cases of clinically and radiologically suspected ovarian masses were included in the study. Thirty cases were evaluated using frozen section and 30 cases using scrape cytology alone. The intraoperative diagnosis of both was compared with the final paraffin section histopathology. Results: The diagnostic accuracy of scrape cytology and frozen section in determining a benign and malignant nature of neoplasm was 96% and 100%, respectively. In 93% of cases, scrape cytology enabled correct categorization of the tumor as surface epithelial, germ-cell tumor, sex cord-stromal, or others. Conclusion: Scrape cytology is an adjunct to frozen section for providing an intraoperative diagnosis; however, in resource-poor settings, it can be used as a stand-alone method for aiding intraoperative decision-making.